TRAINING SCIENCE PROCESS SKILLS USING VIRTUAL LABORATORY ON LEARNING ACID, BASE, AND SALT - Lutfi, Achmad; Hidayah, Rusly (Universitas Negeri Surabaya, 2017)
This study aims to train the Science Process skills to students on learning Acid, Base, and Salt using the Virtual Lab. The research was conducted on the students of SMA Negeri Cerme Gresik in the year 2017/2018. During the student learning using the virtual lab and guided by Student Worksheet, during the learning process conducted an observation of student activity, after learning conducted test of learning result, and questionnaire of student response to the use of the virtual laboratory. The result of the research shows that during the active learning of the students, the learning result reaches completeness, and the students give positive responses to the use of virtual laboratory as the learning medium of acid, base and salt.